Bowel obstruction following ingestion of superabsorbent polymers beads: literature review. (1st February 2022) - Caré, Weniko; Dufayet, Laurène; Paret, Nathalie; Manel, Jacques; Laborde-Casterot, Hervé; Blanc-Brisset, Ingrid; Langrand, Jérôme; Vodovar, Dominique
Abstract: Rationale: Superabsorbent polymers are marketed as toys, and cases of ingestion in children are increasingly reported. Even if these cases are usually considered benign, bowel obstruction has been reported. Objective: To investigate the exposure characteristics, clinical presentation, management, and outcome of patients who developed bowel obstruction following ingestion of superabsorbent polymer-made products. Methods: Databases were searched (no start date − 2020/01/31) using the following keywords: ("superabsorbent" OR "polymer" OR "hydrogel" OR "crystal" OR "jelly" OR "Orbeez" OR "beads") AND ("ingestion" OR "obstruction" OR "perforation") AND ("intestinal" OR "bowel"). All cases of bowel obstruction following superabsorbent polymer-made product ingestion were included. Results: Report selection: We found 25 reports reporting 43 cases of bowel obstruction following superabsorbent polymer-made product ingestion. All the reports were retrospective, including 20 case reports and 4 case series. Patient characteristics and clinical presentation: Age ranged from 6 to 36 months, and the female/male sex ratio was 1.3. The median delay between the ingestion of the product and the onset of the first symptoms (available in only four reports) was 1.0 [0.7;1.8] day (from 15 h to 2 days). The median delay between the onset of gastrointestinal symptoms and hospital admission, available for all but 15 patients, was 3 [2;4] days (from 15 h to 30 days). The reported symptoms were persistent vomiting in all cases, associated with constipation (11/43), diarrhea (1/43), abdominal pain (1/43), and clinically assessed dehydration (14/43). Abdominal palpation found abdominal tenderness or distension in 11/43 and 28/43 patients, respectively. An abdominal mass was palpated in 3/43 patients. Two patients presented with fever, and three patients developed seizures. Characteristics of exposure: Ingestion of superabsorbent polymer-made products was reported by relatives on hospital admission in only 10/43 cases. Based on imaging and/or surgically/endoscopically removed products, all were bead-shaped objects. The median number of beads removed (available in 27/43) was 1 [1–2] (range from 1 to 6). Their median diameter (available in 21/43 patients) at the time of the diagnosis of bowel obstruction – i.e., at hydrated state – was 30 [30;36] mm (range from 25 to 65 mm). Imaging findings: Abdominal radiography, performed in 31/43 patients, never showed evidence of foreign body ingestion Abdominal computed tomography scanning, performed in 10/43 patients, visualized an intraluminal mass in 5/10 cases. Abdominal ultrasound performed in 34/43 patients allowed visualization of a rounded intraluminal image that corresponded to a bead in 28/34 patients but led to a correct diagnosis of foreign body-induced bowel obstruction in only 15/34 cases. One case reported the contributory use of abdominal MRI. Beads were always located in the small bowel (from the duodenum to the terminal ileum). Removal of beads : Bead removal required endoscopy in 2/43 cases and surgery in 41/43 cases (enterotomy or resection in 36/43 and 5/43 cases, respectively). In 3/36 cases, additional enterotomy was performed to remove beads that had not been found during the first surgery. The delay between the onset of gastrointestinal symptoms and removal procedures ranged from 1 to 7 days. Outcome: Except for two fatal cases, the outcome was favorable. Conclusions: Ingestion of superabsorbent polymer-made beads can be responsible for fatal bowel obstruction in children related to the increase in bead size within the intestinal tract. Diagnosis is made difficult by the radiolucent properties of the beads. The management of bowel obstruction probably most often requires endoscopic or surgical procedures. Children under 4 years of age are probably the most at risk of developing bowel obstruction.